Strategies for Exploring Functions from Dynamic Combinatorial Libraries - Chunman Jia; Dawei Qi; Yucang Zhang; Kari Rissanen; Jianwei Li (Germany, 2022)
Dynamic combinatorial chemistry (DCC) is a powerful approach for creating complex chemical systems, giving access to the studies of complexity and exploration of functionality in synthetic systems. However, compared with more advanced living systems, the man‐made chemical systems are still less functional, due to their limited complexity and insufficient kinetic control. Here we start by introducing strategies to enrich the complexity of dynamic combinatorial libraries (DCLs) for exploiting unexpected functions by increasing the species of building blocks and/or templates used. Then, we discuss how dynamic isomerization of photo‐switchable molecules help DCLs increase and alter the systemic complexity in‐situ. Multi‐phase DCLs will also be reviewed to thrive complexity and functionality across the interfaces. Finally, there will be a summary and outlook about remote kinetic control in DCLs that are realized by applying exogenous physical transduction signals of stress, light, heat and ultrasound.